Cities of the biblical world - DeVries, LaMoine F. (Hendrickson Publ., 1997)
This text is designed to introduce students of the Bible to the archaeology, geography, and history of many of the important sites of the Old and New Testament worlds. Many of these sites were centers for trade, religion, defense, culture, industry, and government. DeVries details the development of significant sites from villages and towns to cities, based on how the site could meet the essential needs of the people. The availability of water or arable land, proximity to trade routes, and easily defensible terrain were prime factors in determining a city's prominence. This study concentrates on the cities in Mesopotamia, Aram/Syria and Phoenicia, Anatolia, Egypt, and Palestine during the Old Testament period, and Palestine and the provinces of the Roman world during the New Testament period. Special attention is given to the geographical setting of the city, the history of its development, its relevance to the Bible, its distinguishing features, and any significant archaeological discoveries made at the site.